The EU’S Future Under Scrutiny: Foreign Policy Implications of the EU Energy Diplomacy in the Eastern Mediterranean - Fatma Zeynep Özkurt Dördüncü (Ankara Avrupa Çalışmaları Dergisi, 2024)
This article aims to elucidate the foreign policy implications of the EU’s energy diplomacy endeavors in the Eastern Mediterranean. Building on the conception of “energy diplomacy”, it examines its internal energy policy (in)competences and the external dimension of the EU energy policy. It is argued that because of Russia’s asymmetrical advantage over energy supplies and its geopolitical aggressiveness, the EU is forced to re-regulate its policy takes on energy security and promote diversification of energy supply which cause a gravitation towards new strategic environments such as the Eastern Mediterranean. Herein, this article assesses the effectiveness of the EU’s energy diplomacy; and by applying energy diplomacy model, it evaluates the results of the EU’s endeavors in diversifying external energy supplies and providing energy security.